-3(x-4)=-1

Simple and best practice solution for -3(x-4)=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x-4)=-1 equation:


Simplifying
-3(x + -4) = -1

Reorder the terms:
-3(-4 + x) = -1
(-4 * -3 + x * -3) = -1
(12 + -3x) = -1

Solving
12 + -3x = -1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + -3x = -1 + -12

Combine like terms: 12 + -12 = 0
0 + -3x = -1 + -12
-3x = -1 + -12

Combine like terms: -1 + -12 = -13
-3x = -13

Divide each side by '-3'.
x = 4.333333333

Simplifying
x = 4.333333333

See similar equations:

| 10+c-8c=-10-3c | | 8x+12=-6x-16 | | -6(2)(-1)(-1)= | | y=niga | | 0=x^2-192X+1080 | | 6-3z=-5z-8 | | g^2-2g-8= | | 7-7q=-2q-8 | | 5y+1.5=2y-4 | | 6x+13=-5x-18 | | -9+9p=10p | | -4j+9=-3j | | 2(x+6)+3=5x-7 | | (3x+38)=5x | | 3x+14=-5x-17 | | 3x^9+39x^8+108x^7=0 | | 5-w=-16 | | 7x+10=-5x-16 | | 6x+6+2y=66 | | -5[x+6]=-5x+9 | | 12-21=-9 | | 3-6+2-1+8= | | 0.5x+3=2.5x-6 | | X-5+3x=6x-16 | | 3-3*6+2=l | | 2000=16t^2 | | .09k+13(k+300)=61 | | 2x-y=150 | | 2b+6.7=13.2-8b | | -37y=-36x+1 | | 9y=-4x+1 | | 6-k=7k-5k |

Equations solver categories